Reference ranges and trajectories for blood pressure in pregnancy: findings from a follow-up study based on China Maternal and Newborn's Health Monitoring System - Yijie Ma; Xiao Zhang; Qianzi Che; Keye Wu; Wei Zhao; Huanqing Hu; Qi Yang; Aiqun Huang; Dafang Chen (Taylor & Francis Group, 2020)
Objectives: This study aimed to establish normal blood pressure reference ranges across gestation and maternal characteristics. Methods: We conducted a follow-up study including 29,200 Chinese normal pregnant women. Multilevel restrictive cubic spline models were used to calculate normal blood pressure reference ranges among all population and stratified groups. Results: In all normal pregnancies, the normal reference range of systolic blood pressure were 93.94-118.74 mmHg(2.5th-97.5th) and 97.35-124.63 mmHg at 12 and 37 weeks gestation, respectively while 58.79-74.21 mmHg and 59.19-78.25 mmHg were for diastolic blood pressure at 12 and 37 weeks gestation, which differed in subgroups stratified by prepregnancy body mass index and maternal age. Conclusion: This study provides evidence for blood pressure management in Chinese pregnant women.